Antidiabetic Regimen and Factors Associated with Glycemic Control in Patients with Type 2 Diabetes mellitus in Public Health Centers in Jakarta: A Cross-Sectional Study - Nora Wulandari; Maifitrianti Maifitrianti; Fadilla Muthi’ah; Nava Nur Disya (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Background:The glycemic control of diabetes mellitus patients is affected by many factors, including its antidiabetic regimen. Objectives: This study aimed to describe the antidiabetic regimen used in patients with T2DM in the public health centres in Jakarta and to evaluate the association of the regimens and other factors with glycemic control. Methods:This was a cross-sectional study conducted in thirteen public health centres in Jakarta with HbA1C of ≤ 7% indicating good glycemic control and > 7% poor glycemic control. The univariate analysis tests were used to analyze factors that potentially associate with glycemic control. Association between antidiabetic regimen and glycemic control were done by Pearson chi-square test and Fisher exact test.Results:Combination of sulfonylureas and biguanides was the most frequent antidiabetic regimen prescribed to the patients. Univariate analysis showed that age, duration of T2DM, route of administration, number of antidiabetics, and number of other daily regular drugs significantly (P<0.05) related to glycemic control.Sulfonylurea and biguanides as monotherapy were significantly (P<0.05) associated with good glycemic control. Conclusion:Sulfonylurea and biguanide as monotherapy were found to be associated with good glycemic control. In contrast, the combination of and with the two did not show the same.